2019
DOI: 10.31234/osf.io/jpq6f
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intermittent absence of control during reinforcement learning interferes with Pavlovian bias in action selection

Abstract: The ability to control the occurrence of rewarding and punishing events is crucial for our well-being. Two ways to optimize performance are to follow heuristics like Pavlovian biases to approach reward and avoid loss, or to rely more on slowly accumulated stimulus-action associations. Although reduced control over outcomes has been linked to suboptimal decision-making in clinical conditions associated with learned helplessness, it is unclear how uncontrollability of the environment is related to the arbitratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…This finding is consistent with the original report describing the data set [20], which showed that the Pavlovian weight governing action selection could be partially predicted from midfrontal theta power, a finding further supported by subsequent research [27]. A recent study [26] attempted to more directly link midfrontal theta to controllability using a "learned helplessness" design in which one group of subjects intermittently lost control over outcomes by "yoking" the outcomes to those observed by a control group. The control group exhibited the same relationship between Pavlovian weight and midfrontal theta observed in earlier studies, whereas the yoked group did not (however, it must be noted that a direct comparison did not yield strong evidence for group differences).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This finding is consistent with the original report describing the data set [20], which showed that the Pavlovian weight governing action selection could be partially predicted from midfrontal theta power, a finding further supported by subsequent research [27]. A recent study [26] attempted to more directly link midfrontal theta to controllability using a "learned helplessness" design in which one group of subjects intermittently lost control over outcomes by "yoking" the outcomes to those observed by a control group. The control group exhibited the same relationship between Pavlovian weight and midfrontal theta observed in earlier studies, whereas the yoked group did not (however, it must be noted that a direct comparison did not yield strong evidence for group differences).…”
Section: Discussionsupporting
confidence: 87%
“…In previous work on this same data set [20], and in follow-up studies [27,26], frontal theta was implicated in the suppression of the Pavlovian influence on choice. Consistent with these previous findings, we found that frontal theta power decreased with the Pavlovian weight [top vs. bottom quantile: t(31) = 2.09, p < 0.05; Fig 3].…”
Section: Eeg Resultsmentioning
confidence: 68%
See 1 more Smart Citation
“…The idea that inferences about controllability underlie learned helplessness has been incorporated into formal Bayesian models that share some properties with the model proposed in this paper 30 . In addition, recent work has shown that outcome controllability manipulations can induce learned helplessness in humans, and also enhance Pavlovian biases in a reinforcement learning context 31 .…”
Section: Variancementioning
confidence: 99%